2016
DOI: 10.1186/s40816-016-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an ethanolic extract of Berberis vulgaris fruits on hyperglycemia and related gene expression in streptozotocin-induced diabetic rats

Abstract: Background: Finding a treatment for diabetes that does not have side effects has remained elusive. Among natural agents, much attention has been focused on phenolic compounds. For both their medicinal and nutritional value, barberry plants are of particular interest. Berberis vulgaris is known for its medicinal benefits in Iranian traditional medicine. In this study, we investigated the biological activities of B.vulgaris in a rodent model of experimentally induced diabetes. Method: The fasting blood glucose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…These results indicated that barberry can improve hyperglycemia in diabetic rats by inhibition of gluconeogenesis. ( Hemmati et al, 2017 ). These results were in agreement with our results…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that barberry can improve hyperglycemia in diabetic rats by inhibition of gluconeogenesis. ( Hemmati et al, 2017 ). These results were in agreement with our results…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations of the anti-diabetic effects of acankoreagenin are needed to be determined in diabetic rats in vivo [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in diabetic rats, the beneficial effects of B. vulgaris extracts showed positive effects in attenuating the side effects of T2DM (Karami et al, 2016), ameliorating oxidative stress (Hemmati et al, 2016), decreasing the liver damage by influencing hepatic histopathological and biochemical markers (Rahimi-Madiseh et al, 2017), and showed that the serum cholesterol and serum triglycerides levels were decreased (Meliani et al, 2011).…”
Section: In Vivo Activities Against Diabetes and Metabolic Diseasesmentioning
confidence: 99%